2011
DOI: 10.1007/s00441-011-1187-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone on steroid content, proliferation and apoptosis in the chicken ovary during sexual maturation

Abstract: The present study was undertaken to examine in vivo the effect of growth hormone (GH) on progesterone and estradiol levels and on cell proliferation and apoptosis in the chicken ovary during sexual maturation. Hy-Line chickens (10 weeks old) were injected three times a week with 200 μg recombinant chicken GH (cGH) per kilogram body weight until sexual maturity. GH treatment significantly increased ovarian weight at 16 weeks of age, i.e., ~1 week before onset of egg laying. The progesterone content in the ovary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 68 publications
(79 reference statements)
4
28
0
1
Order By: Relevance
“…GH is produced primarily in the pituitary by the somatotrophic cells of the mesoadenohypophysis, although it is well established that some extrapituitary tissues express the GH gene, and that its product is not released into the systematic circulation but acts locally in an autocrine or paracrine manner (26). Although GH is expressed in the gonads of mammals (13,14), birds (15)(16)(17)(18), and fish (27,28), the function of gonadal GH in regulating growth has not been determined. Our results indicate that the gonads play an important role in the regulation of body growth in both male and female tilapia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GH is produced primarily in the pituitary by the somatotrophic cells of the mesoadenohypophysis, although it is well established that some extrapituitary tissues express the GH gene, and that its product is not released into the systematic circulation but acts locally in an autocrine or paracrine manner (26). Although GH is expressed in the gonads of mammals (13,14), birds (15)(16)(17)(18), and fish (27,28), the function of gonadal GH in regulating growth has not been determined. Our results indicate that the gonads play an important role in the regulation of body growth in both male and female tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the release of GH from ectopically transplanted gonads stimulates growth. GH and IGF-I are expressed in the testis of human and chicken (17)(18)(19)(20)(21), and the gonads might produce both GH and IGF-I, although there might be differences between species. The roles of these hormones produced from the gonads in growth are not clearly understood, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, yellow hierarchical follicles were present in the ovaries of most GH treated hens but not in the control hens ( Fig. 1), suggesting the involvement of GH in the selection of small prehierarchical follicles into hierarchy of yellow preovulatory follicles (Hrabia et al, 2011). In other experiments Donoghue et al (1990) found that GH injections for 3 weeks to older egg laying White Leghorn hens did not affect egg production, but significantly improved eggshell quality.…”
Section: Physiological Evidence Of Growth Hormone-controlled Avian Rementioning
confidence: 94%
“…Moreover, a role for pituitary GH in the function of the ovary is also supported by an increase in the number of small ovarian follicles after GH administration to laying hens (Williams et al, 1992). Similarly, injections of recombinant chicken GH (cGH) to chickens prior to the onset of egg laying resulted in increased ovarian weight (13.5 ± 6.14 g vs 0.89 ± 0.14 g or 7.70 ± 4.17 g vs 1.10 ± 0.12 g, dependently on experiment) about one week before sexual maturity (Hrabia et al, 2011). Moreover, yellow hierarchical follicles were present in the ovaries of most GH treated hens but not in the control hens ( Fig.…”
Section: Physiological Evidence Of Growth Hormone-controlled Avian Rementioning
confidence: 98%